Edukasi Gizi dan Penyuluhan Produk PMT sebagai Upaya Pencegahan Masalah Gizi pada Balita di Desa Blang Beurandang Aceh Barat - Safrida, Safrida; Mulyani, Itza; Masitah, Ravi; Duana, Maiza; Marniati, Marniati (Lok Seva: Journal of Contemporary Community Service, 2025)
Observation results in Blang Beurandang Village, Johan Pahlawan, West Aceh, in 2025 revealed several cases of malnutrition in toddlers, specifically three toddlers experiencing stunting, two toddlers experiencing wasting, and two toddlers being underweight. As a result, it not only inhibits the physical and cognitive growth of children but can even cause death. One effort to overcome this is to provide nutrition education. This community service activity was carried out in Blang Beurandang Village, Johan Pahlawan, involving mothers of toddlers and village cadres. The method used is Community Rural Participatory, including the assessment stages (recapitulation of initial anthropometric measurement data and secondary data), planning stages (educational media, PMT), and implementation stages (measuring the level of knowledge of the target group using pretest-posttest before and after being given counseling). The results of the activity showed the highest prevalence, namely underweight at 18.42%, followed by stunting at 15.79%, wasting at 7.89%, and the lowest, namely obesity and overnutrition at 2.63%. Then, in measuring the level of knowledge among mothers about stunting, wasting, underweight, and the role of PMT, with a total of 14 mothers of toddlers as respondents, an increase in knowledge was observed after nutrition counselling, specifically from 7.1% of respondents with good knowledge, increasing to 57.1%. PMT products, in the form of chicken-filled tempeh balls, were well received by the target group during the activity. However, ongoing mentoring, monitoring, and education efforts are necessary to ensure that knowledge about nutrition and PMT processing is effectively applied in everyday life, particularly in the practice of providing food to children and managing family food.